Air pollution accelerates the development of obesity and Alzheimer’s disease: the role of leptin and inflammation - a mini-review - Campolim, Clara Machado; Schimenes, Bianca Camilo; Veras, Mariana Matera; Kim, Young-Bum; Prada, Patricia Oliveira (Frontiers in Immunology, 2024)
Air pollution is an urgent concern linked to numerous health problems in low- and middle-income countries, where 92% of air pollution-related deaths occur. Particulate matter 2.5 (PM2.5) is the most harmful component of air pollutants, increasing inflammation and changing gut microbiota, favoring obesity, type 2 diabetes, and Alzheimer's Disease (AD). PM2.5 contains lipopolysaccharides (LPS), which can activate the Toll-like receptor 4 (TLR4) signaling pathway. This pathway can lead to the release of pro-inflammatory markers, including interleukins, and suppressor of cytokine signaling-3 (SOCS3), which inhibits leptin action, a hormone that keeps the energy homeostasis. Leptin plays a role in preventing amyloid plaque deposition and hyperphosphorylation of tau-protein (p-tau), mechanisms involved in the neurodegeneration in AD. Approximately 50 million people worldwide are affected by dementia, with a significant proportion living in low—and middle-income countries. This number is expected to triple by 2050. This mini-review focuses on the potential impact of PM2.5 exposure on the TLR4 signaling pathway, its contribution to leptin resistance, and dysbiosis that exacerbates the link between obesity and AD.